2008
DOI: 10.1093/ajcn/87.6.1616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of docosahexaenoic acid–rich n−3 fatty acid supplementation on cytokine release from blood mononuclear leukocytes: the OmegAD study

Abstract: AD patients treated with DHA-rich n-3 FAs supplementation increased their plasma concentrations of DHA (and EPA), which were associated with reduced release of IL-1beta, IL-6, and granulocyte colony-stimulating factor from PBMCs. This trial was registered at clinicaltrials.gov as NCT00211159.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 35 publications
7
93
0
2
Order By: Relevance
“…As reported previously ( 28 ), at study entry DHA and EPA concentration in plasma were not signifi cantly different between the 3 FA and the placebo group. In the 3 FA group, give rise to the highly anti-infl ammatory metabolites resolvins and protectins, which interacts with prostaglandin synthesis ( 11 ).…”
Section: Plasma Fatty Acidssupporting
confidence: 81%
See 2 more Smart Citations
“…As reported previously ( 28 ), at study entry DHA and EPA concentration in plasma were not signifi cantly different between the 3 FA and the placebo group. In the 3 FA group, give rise to the highly anti-infl ammatory metabolites resolvins and protectins, which interacts with prostaglandin synthesis ( 11 ).…”
Section: Plasma Fatty Acidssupporting
confidence: 81%
“…Samples were incubated overnight (22 h) in 37°C humidifi ed 5% CO 2 atmosphere. Subsequently, cells were centrifuged, and supernatants were collected and stored in Ϫ 80°C before cytokine determinations ( 28 ).…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, DHA/EPA dietary supplementation in healthy subjects blunted the endocrine stress response and the increase in body temperature, with or without impact on cytokine production after bacterial endotoxin administration (Ferguson et al, 2014;Michaeli et al, 2007). AD patients supplemented with a DHA-rich diet display reduced release of proinflammatory cytokines (IL-1β, IL-6, GM-CSF) from stimulated peripheral blood mononuclear cells (Vedin et al, 2008). In addition, students with DHA/EPA supplementation show a decreased anxiety and proinflammatory cytokines production only in ex vivo stimulated immune cells but not in the plasma (Kiecolt-Glaser et al, 2011).…”
Section: N-pufas Neuroinflammation and Cognitive Disordersmentioning
confidence: 99%
“…These effects have been ascribed to the improvement of cardiovascular risk profiles, resulting in disease prevention21; however, the data on IHD and hypertension are less robust. Clinical trials in post–myocardial infarction patients have suggested that DHA, specifically, may exert a therapeutic effect, particularly on hypertension and the risk of reinfarction,22 although this has not been shown unequivocally or linked with atherosclerotic plaque stabilization/regression 23, 24. DHA supplementation decreased blood pressure in spontaneously hypertensive rats25, 26 and in a dog model of hypertension,27 but no data are available for mouse models with atherosclerosis.…”
mentioning
confidence: 99%